4 - Challenges for the Opposition and Democratisation in Tanzania: A View from the Opposition: by Jonas Ewald & Lennart Wohlgemuth - Awald, Jonas; Wohlgemuth, Lennart (Africa Development, 2021)
In the period after 1990, a massive return to liberalised forms of politics has taken place and has been largely centred around the dismantling of one party- regimes, the termination of a large number of military-led or dominated governments, the embrace of a multiparty political framework, the introduction of an independent media, the restoration of some basic freedoms to the people of the countries concerned and the convening of multi-party elections. This development was so widespread and overwhelming that it was seen by many observers as the beginning of Africa’s second liberation (Olukoshi 1998; Gyimah-Boadi 2004; Mkandawire 2006). Potential gains to the peoples from the liberalisation of their national political spaces were undermined since the 1980s by the conditions set by outside suppliers of necessary resources, combined with internal challenges in terms of weak institutions, civil society and media as well as lack of a tradition of multi- party democracy and general poverty. Matters appear to have been worsened by the fact that in many African countries the promise which the opposition once represented as the bearer of the hopes and aspirations of the people has substantially faded away. Several factors have contributed to weaken and, in some cases, discredit the opposition in much of Africa’s ongoing experience with multiparty politics. This is a serious development that begs for further investigation; as the development of a healthy and vigorous opposition is a major part of a democratic framework. In this study, we will see how the situation in Tanzania has evolved over the past 17 years of multi-party development; based on rather unique interviews with Professor Ibrahim Lipumba, leader of one of Tanzania’s major opposition parties.